Optimasi Keuntungan Industri Rumah Tangga Tahu dan Tempe Di Desa Murung Kupang Kecamatan Babirik Kabupaten Hulu Sungai Utara - Azwar Saihani (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2016)
This study aims to (i) know the optimal benefits of tofu and tempeh making business with limited resources, (ii) conduct sensitivity analysis on the optimal conditions of the benefits of tofu and tempeh business. This research was conducted in Murung Kupang Village, Babirik District, North Hulu Sungai Regency. The method of collecting data uses a case study by interviewing Pak Sarwani to obtain the necessary data. The point of optimal home industry and tofu solutions occurs at coordinates (29.66), (357.47), this means that optimal benefits occur when production of tofu (X1) is 29.66 prints of tofu and (X2) of 357, 47 tempe cut each time the product. While the optimal amount of profit obtained is USD 1357,941 per one production in one day. Maximum and minimum limit for optimization of tempe and tempeh tofu industry. The maximum profit margin exits between 43,819 to 27,200 and the minimum margin of profit margin between 70,317 to 43,819, while the maximum limit of profit margin for tempe that has not been used is between 911,222 to 567,850, the minimum tempe profit margin between 1,468 to 911,222, and the translation value constraint function shadow 1 (soybeans) it appears that if the resource (right value) exceeds the 10% constraint function, ie from 102 663 933.33 to the optimal value of Rp 161,261, increasing from Rp 1,357,941 to Rp 1,519,202